Wet Brewers' Grains for Beef Cattle - Megan Thomas; Matt Hersom; Todd Thrift; Joel Yelich (EDIS, 2010)
AN241, a 4-page fact sheet by Megan Thomas, Matt Hersom, Todd Thrift, and Joel Yelich, describes this by-product of the beer-brewing industry — feed characteristics, considerations for use, and feeding guidelines. Includes references. Published by the UF Department of Animal Sciences, May 2010.